Referral assessment and patient waiting time decisions in specialized mental healthcare: an exploratory study of early routine collection of PROM (LOVePROM) - Fan Yang; Knut Reidar Wangen; Mattias Victor; Ole André Solbakken; Per Arne Holman (BMC, 2022)
Abstract Background Norway has prioritized health services according to the principle of "severity of conditions", where waiting time reflects patients' medical urgency. We aim to investigate if the "severity-of-condition" principle performs well in the priority setting of waiting time, between and within groups of patients using community mental health services. We also aim to investigate the association between patients' diagnoses and symptom severity at the start of treatment and the corresponding waiting time. Methods The study analyzed routine data from Lovisenberg electronic Patient-Reported Outcome Measurement (LOVePROM) at Lovisenberg Diaconal Hospital in Norway. We estimated patient-reported severity by using Clinical Outcomes in Routine Evaluation - Outcome Measure (CORE-OM), together with patients' diagnoses to identify patients' needs in general. To assess the performance of current prioritization, we compared waiting times for patients with major depressive disorder and their maximum recommended waiting time. Multivariate regression models were used to assess the association between patient-reported severity, their diagnosis, and waiting times. Results Of the 6108 mental health disorder patients, patients with moderate to severe conditions waited seven weeks, while patients with mild conditions or below clinical cutoff waited 8 weeks. Included in the sample, 1583 were diagnosed with depression. Results indicated that patients with moderate and severe depression had a slightly shorter wait-time than patients with mild depression. However, 32.4% patients with moderate depression and 83.3% patients with severe depression, waited longer than their maximum recommended waiting time. CORE-OM identified depressive patients with risk-to-self harm, who had a 0.84 weeks shorter wait-time. These results were also applied to patients with other common mental health disorders. Conclusion Overall, patients waited in accordance with the "severity of condition" principle, but the trend was not strong. Therefore, we advocate that there is substantial room for quality improvements in priority setting on waiting time. We suggest further research should investigate if routine collection of PROM and assessment of referral letters, can better inform specialists when deciding on waiting time.